2019
DOI: 10.3390/cancers12010001
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Gene Signature-Based Model Predicts Biochemical Recurrence-Free Survival in Prostate Cancer Patients after Radical Prostatectomy

Abstract: Currently, decision-making regarding biochemical recurrence (BCR) following prostatectomy relies solely on clinical parameters. We therefore attempted to develop an integrated prediction model based on a molecular signature and clinicopathological features, in order to forecast the risk for BCR and guide clinical decision-making for postoperative therapy. Using high-throughput screening and least absolute shrinkage and selection operator (LASSO) in the training set, a novel gene signature for biochemical recur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 39 publications
(44 reference statements)
1
24
0
Order By: Relevance
“…Using the training and validation datasets, we first identified 6 preserved PCa-driven modules and then screened 9 prognosis-related genes (including 3 lncRNAs: DLG5-AS1, MAGI2-AS3, and RHPN1-AS1; and 6 mRNAs: GINS2, NLGN2, EBNA1BP2, MELK, EIF5AL1, and G6PC3) from these modules to construct the risk score. The ROC curve analysis demonstrated the prediction accuracy of this molecular risk score was higher than that of clinical indicators (the Gleason score [AUC = 0.945 vs.0.57], PSA [AUC = 0.945 vs.0.578], and combined [AUC = 0.945 vs.0.673]), which was in line with the studies of Li et al [ 9 ], Shi et al [ 10 ], Huang et al [ 11 ], and Xu et al [ 12 ]. More importantly, our integrated model seemed to be more effective than the single mRNA model (Xu et al: 4-mRNA, AUC = 0.945 vs.0.904 [ 26 ]) for OS prediction, which was also observed in our study (AUC = 0.945 vs.0.81) ( Figure 7 ).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Using the training and validation datasets, we first identified 6 preserved PCa-driven modules and then screened 9 prognosis-related genes (including 3 lncRNAs: DLG5-AS1, MAGI2-AS3, and RHPN1-AS1; and 6 mRNAs: GINS2, NLGN2, EBNA1BP2, MELK, EIF5AL1, and G6PC3) from these modules to construct the risk score. The ROC curve analysis demonstrated the prediction accuracy of this molecular risk score was higher than that of clinical indicators (the Gleason score [AUC = 0.945 vs.0.57], PSA [AUC = 0.945 vs.0.578], and combined [AUC = 0.945 vs.0.673]), which was in line with the studies of Li et al [ 9 ], Shi et al [ 10 ], Huang et al [ 11 ], and Xu et al [ 12 ]. More importantly, our integrated model seemed to be more effective than the single mRNA model (Xu et al: 4-mRNA, AUC = 0.945 vs.0.904 [ 26 ]) for OS prediction, which was also observed in our study (AUC = 0.945 vs.0.81) ( Figure 7 ).…”
Section: Discussionsupporting
confidence: 89%
“…Shi et al established a prognostic risk score based on 9 protein-coding genes. Receiver operating characteristic (ROC) analysis indicated that the prediction accuracy of this risk score for BCR-free survival was higher than that of Gleason score (area under curve (AUC) = 0.836 vs.0.742) and pathological T stage (AUC = 0.836 vs.0.780) [ 10 ]. Similar superiority of the molecular risk score was also observed in the study of Huang et al who found the four-long noncoding RNA- (lncRNA-) based risk score was independent of the American Joint Committee on Cancer T stage and Gleason score for the prediction of BCR-free survival and disease-free survival.…”
Section: Introductionmentioning
confidence: 99%
“…The LASSO regression analysis is an accepted method for the reduction in high dimensional data, as described previously 13 . In this study, LASSO regression analysis was performed by R package “glmnet” to filtrate most powerful prognostic markers of m1A-related regulatory genes, and disease risk prediction score was established in HCC patients.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, more ideal biomarker and predictive model are warranted to be developed. Recent studies in many malignancies, including PCa, suggested that multigene classifier or gene signature can make a good prediction of tumor prognosis [ 9 11 ]. However, limited robust signature has been constructed to predict early BCR [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%